Multi-scale dynamics of particle dampers using wavelets: Extracting particle activity metrics from ring down experiments. (18th August 2019) - Gnanasambandham, C.; Stender, M.; Hoffmann, N.; Eberhard, P.
Abstract: In this work, the concept of temporal multi-scale analysis is applied to particle damper (PD) systems in order to characterize their damping performance. For this purpose discrete wavelet transform (DWT) is used to separate the dynamics on different scales contained in univariate time-series data. These data are generated from classical ring-down experiments of a vibrating leaf spring damped by a PD. The analysis reveals the presence of micro fluctuations, which are structural vibrations induced by solid particle activity, superimposed onto the first modes of the structure. In order to quantify the degree of relative motion present, a particle activity metric is introduced based on the fast and slow dynamics separated by the DWT. A physical interpretation of the solid particle activity metric is provided using discrete element method (DEM) simulations. The particle activity based dissipation metric is compared with classical dissipation metrics and shows good agreement. Hence, the proposed methodology allows for characterizing PD systems by signal processing of classical vibration data that can be gathered at low costs. In a case study, the effect of container length and the presence of an added liquid in the container on the solid particle activity is studied. Higher levels of solid particle activity are observed for the case where the damper is filled with both solid particles and liquid fillings compared to the purely solid particle case.